Effect of soy on bone turn-over markers in men with type 2 diabetes and hypogonadism – a randomised controlled study. Issue 1 (December 2017) - Sathyapalan, T.; Aye, M.; Rigby, A.; Fraser, W.; Kilpatrick, E.; Atkin, S.
Abstract Type 2 diabetes (T2DM) is associated with increased risk of fractures. Soy supplementation has been shown to have a beneficial effect on bone turnover markers (BTM) in postmenopausal women. However, the effect of soy supplementation on BTM in T2DM and particularly in men is unclear. We performed an analysis of a randomized double blind parallel study of 200 men with T2DM treated with soy, either with or without isoflavones. Outcome measures were type I collagen crosslinked beta C-telopeptide (βCTX), and type 1 procollagen-N-propeptide (P1NP). The men, with a total testosterone <12 nmol/L, were treated with 15 g soy protein containing 66 mg of isoflavones (SPI) or 15 g soy protein alone without isoflavones (SP) daily for three months. There was a 15% reduction in βCTX after three months of SPI compared to SP supplementation. There was no significant difference in P1NP with either SPI or SP supplementation. There was a significant linear correlation between the reduction in βCTX in the SPI group with the reduction in HbA1c (r2  = 0.42; p = 0.04) and HOMA-IR (r2  = 0.54; p = 0.02). Our study indicates that there was a significant reduction in bone resorption following 3 months of SPI supplementation that correlated with an improvement of glycemic control in men with T2DM.